The "New Wars" Paradigm - Mach, Jiří (2017)
This thesis aims to find evidence of “New Wars” paradigm present in contemporary conflict. First, methodological concept of “New Wars” is elucidated with special emphasis on identity politics. Changing nature of global order is anchored using the works of Joseph Nye and his concepts of power diffusion and power transition. Nature of war is contested, drawing from the debates on Westphalian notion of war and concepts put forth by Clausewitz. Ukrainian conflict is scrutinized as potential “New Wars” conflict. The notion of Strategic Narratives is then used to shed light on certain mechanisms behind the identity politics. The last chapter aims to illustrate the wider Russian attempts to contest Western narratives.